Zoom slide presentation on basic electrical & electronics subjects Class X Electrical Engineering Department SMK Darussalam Makassar - Hasyim, Nurhikmah; Hakim, Abdul; Agung Nuh, Muhammad Vaqhi (Jurnal Inovasi Teknologi Pendidikan, 2024)
The research aims to: (1) Identify the need for interactive multimedia presentations using Microsoft Office PowerPoint version 2019 (2) Design interactive multimedia presentations using Microsoft Office PowerPoint version 2019 (3) Produce interactive multimedia presentation media using Microsoft Office PowerPoint version 2019 which are valid and practical. The method used is research and development with the Alessi and Trollip models. The results of the needs analysis show inferior qualifications. The validation results of media and design experts show excellent qualifications and are at a very valid category level. At the same time, the design aspect is in good qualification and is at the valid category level. The results of the content expert validation show excellent qualifications and are at the very valid category level. Product development was then handed over to 3 students who were selected based on learning achievement by the subject teacher. The results of the individual test questionnaire show that the percentage of student 1 is in very satisfactory qualifications, the percentage of student 2 is in satisfactory qualifications, the percentage of student 3 is in very satisfactory qualifications and is at the practical category level so that the 2019 interactive multimedia PowerPoint presentation media does not need to be revised. The product development was then handed over to 9 selected students to be divided into 3 groups consisting of 3 students. The 2019 interactive multimedia PowerPoint presentation media is in good qualifications and at the practical category level. Assessment results. The teacher of the basics of electricity shows a percentage of 100% achievement level, has very good qualifications, and is at the level of a very practical category to use.